Concordance in evolutionary history of threatened plant and insect populations warrant unified conservation management approaches. (June 2016) - Moir, Melinda L.; Coates, David J.; Kensington, W. Jason; Barrett, Sarah; Taylor, Gary S.
Abstract: Threatened organisms may act as host to a suite of dependent organisms, which are potentially cothreatened, yet management is rarely coordinated between host and dependent species. Here, we test the congruency of patterns of genetic structure between two critically endangered interacting taxa; the feather-leaf banksia ( Banksia brownii R.Br.), and its host-specific herbivorous plant-louse Trioza barrettae Taylor & Moir, to establish whether conservation actions should be implemented jointly for both species. We also examine the role of host population size and fire history on the density of psyllids on host plants. We show that the patterns of mtDNA variation in T. barrettae and microsatellite variation in both species support the presence of at least two conservation units across each species, with the microsatellites also showing a high evolutionary congruency between plant and insect populations. The extinction of divergent B. brownii populations, therefore, is likely to have resulted in the extinction of divergent plant-louse populations. Larger populations of host plant (> 150) and more recent fire history (< 20 years since fire) are important factors in maintaining T. barrettae densities. High molecular congruency indicates the importance of considering patterns of genetic diversity of source material from both host and dependent organisms for ex situ conservation, in situ supplementations and reintroductions. As dependents such as T. barrettae are often lost to extinction before their host, considering the conservation of dependent biota in the early stages of species management is paramount. Graphical abstract: Highlights: We examine two interacting critically endangered species for molecular congruency in genetic structure across populations High molecular congruency occurred between a Banksia plant and its herbivorous plant-louse Such patterns in genetic diversity should be considered in in situ and ex situ conservation management Dependents are often lost before their host; the plant-louse has been extinguished from four extant Banksia populations The conservation of dependent biota in the early stages of host management is paramount to prevent local extinctions